Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

Decentralized Brain Age Estimation Using MRI Data - Sunitha Basodi; Rajikha Raja; Bhaskar Ray; Harshvardhan Gazula; Anand D. Sarwate; Sergey Plis; Jingyu Liu; Eric Verner; Vince D. Calhoun (Neuroinformatics, 2022)

Federated Analysis of Neuroimaging Data: A Review of the Field - Kelly Rootes-Murdy; Harshvardhan Gazula; Eric Verner; Ross Kelly; Thomas DeRamus; Sergey Plis; Anand Sarwate; Jessica Turner; Vince Calhoun (Neuroinformatics, 2022)

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

Decentralized Multisite VBM Analysis During Adolescence Shows Structural Changes Linked to Age, Body Mass Index, and Smoking: a COINSTAC Analysis - Harshvardhan Gazula; Bharath Holla; Zuo Zhang; Jiayuan Xu; Eric Verner; Ross Kelly; Sanjeev Jain; Rose Dawn Bharath; Gareth J. Barker; Debasish Basu; Amit Chakrabarti; Kartik Kalyanram; et al. (Neuroinformatics, 2021)